Transfusion‐associated circulatory overload prevention: a retrospective observational study of diuretic use. Issue 4 (8th March 2018) - Lin, Y.; Cohen, R.; Armali, C.; Callum, J.; Cserti‐Gazdewich, C.; Lieberman, L.; Pendergrast, J.
Abstract : Background and Objectives: Approaches to preventing transfusion‐associated circulatory overload (TACO) include the use of diuretics. The purpose of this study was to determine how commonly diuretics are prescribed in patients receiving a red‐blood‐cell (RBC) transfusion. Materials and Methods: This was a retrospective study of 200 adult inpatient RBC transfusion orders, 50 consecutive at each of four academic institutions. Only the first transfusion order for each patient was included. Only 1 or 2 unit orders were included. The primary outcome was the percentage of patients receiving furosemide peri‐transfusion. Secondary objectives included the dose, route, and timing of furosemide and the association of clinical factors with ordering furosemide. Results: The median age was 62·5 years (IQR 53, 73), and 52% were female. Peri‐transfusion furosemide was ordered in 16% (95% CI 11–21%). The most common dose was 20 mg (55%), the route intravenous (90%) and timing post‐transfusion (74%). At least one risk factor for TACO was present in 55% of patients: renal dysfunction (33%), older than 70 years (28%), history of congestive heart failure (18%), ejection fraction <60% (16%) and diastolic dysfunction (5%). Low haemoglobin as an indication for transfusion (OR 4·2; 95% CI 1·4–12·8) and diuretics on admission (OR 3·5; 95% CI 1·5–8·0) were associated with ordering furosemide peri‐transfusion. Conclusions: Furosemide is not routinely ordered for RBC transfusion, even in patients with risk factors for TACO. Studies assessing the safety, efficacy, optimal dose, and timing of furosemide in preventing TACO are justified.